Does the Fast Alcohol Screening Test Accurately Distinguish Between Harmful and Severely Dependent Tiers of Alcohol Misuse?. (23rd March 2021) - John, Bev; Newstead, Simon; Heirene, Robert; Hodgson, Ray; Roderique-Davies, Gareth
Abstract: Aims: Primary aim: to determine the efficacy of FAST (the Fast Alcohol Screening Test) for detecting harmful and dependent levels of alcohol use. Secondary aim: to compare the performance of the FAST to two short forms of the Alcohol Use Disorder Identification Test (AUDIT): the AUDIT-C and AUDIT-3. Methods: Data from 3336 individuals in South Wales, compiled from full AUDIT datasets, were examined. AUROC analysis, alongside measures of sensitivity and specificity of the FAST, AUDIT-C and AUDIT-3 were utilized for the identification of harmful and dependent alcohol use. Results: The FAST demonstrated efficacy in the identification of harmful and dependent levels of alcohol use, with superior performance to both the AUDIT-C and AUDIT-3. Conclusion: The present paper demonstrates the potential of the FAST as a cost- and time-effective method for appropriate screening and signposting in the stepped care model utilized by many health care and treatment services. Further studies are needed to ensure validity, both within the general population and for specific services and populations. Abstract : Short Summary : The FAST (Fast Alcohol Screening Test) (a brief screen for alcohol consumption, dependence and harm) demonstrates efficacy in its ability to identify and distinguish between both harmful and severely dependent tiers of alcohol use, within a population which predominantly exhibits risk-related alcohol usage. The FAST exhibits superior performance, in this respect, to the AUDIT-C and AUDIT-3 (which measure consumption only), providing additional evidence to further highlight the importance of not solely relying on alcohol consumption to classify tiers of harm.